New trends in pharmacogenomic strategies against resistance development in microbial infections. (November 2008) - Ohlsen, Knut; Dandekar, Gudrun; Schwarz, Roland; Dandekar, Thomas
This review summarizes some of the new trends in the fight against drug resistant bacteria. We review Gram-positive (e.g., S.aureus ) and Gram-negative (e.g., Pseudomonas aeruginosa, Helicobacter pylori ) bacteria, the current antibiotic resistance situation, as well as resistance spread and some recently discovered resistance mechanisms, such as those based on integrons and complex transposons. We then summarize several current routes to identify new drugs such as cationic antimicrobial peptides, novel acyldepsipeptides, RNA aptamers and lipopeptides. New drug strategies to treat resistant pathogens include eliciting growth in dormant bacteria, or a new way to attack efflux systems. Typical approaches from pharmacogenomics combined with systems biology and bioinformatics support these routes (simulations, metagenomics and metabolic network modeling), as well as the patient treatment (e.g., haplotyping and immune response).